2022
DOI: 10.1002/pc.26539
|View full text |Cite
|
Sign up to set email alerts
|

Study of environmental behavior and its effect on solid particle erosion behavior of hierarchical porous activated carbon‐epoxy composite

Abstract: Porous carbon materials have versatile physical and chemical characteristics; however, these materials are not be fully exploited as reinforcements in polymer composites. The present investigation focuses on extraction of hierarchical porous carbon and its utilization in polymer composite in order to enhance the erosion wear resistance and hardness of polymer composite. The current research work also demonstrates the wear behavior of the hierarchical porous carbon epoxy composite when exposed to different envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 53 publications
(71 reference statements)
1
4
0
Order By: Relevance
“…After the 30° impingement angle, it was determined that the erosion rate decreased in line with the increase in the angle between the nozzle and the pipes from oblique to vertical impact for both test positions. In particular, the 30° and 45° data exhibited close erosion resistance and are compatible with the literature; that is, a situation similar to ductile-prone erosional wear has occurred [ 12 , 23 ]. In other words, in these tests, the scraping effect of oblique impact was dominant, and separation from the surface was accelerated.…”
Section: Resultssupporting
confidence: 85%
“…After the 30° impingement angle, it was determined that the erosion rate decreased in line with the increase in the angle between the nozzle and the pipes from oblique to vertical impact for both test positions. In particular, the 30° and 45° data exhibited close erosion resistance and are compatible with the literature; that is, a situation similar to ductile-prone erosional wear has occurred [ 12 , 23 ]. In other words, in these tests, the scraping effect of oblique impact was dominant, and separation from the surface was accelerated.…”
Section: Resultssupporting
confidence: 85%
“…Erosion wear rate is measured by the following formula. Erosion wear rate0.25em()normalg/normalggoodbreak=w1w2w where, w 1 is the weight of the sample before erosion w 2 is weight of composite sample after the erosion, and w is the weight of the erodent used. [ 40 ]…”
Section: Methodsmentioning
confidence: 99%
“…[39] 2.5 | Erosion wear test Solid particle erosion wear behavior of biochar epoxy composite materials was investigated using erosion test where, w 1 is the weight of the sample before erosion w 2 is weight of composite sample after the erosion, and w is the weight of the erodent used. [40] F 3 | RESULTS AND DISCUSSIONS…”
Section: Characterization Of Biochar Carbon Materialsmentioning
confidence: 99%
“…Additionally, epoxy resin, being highly resistant, is a viable option for producing filtration materials that withstand chemical cleaning methods when plugged with contaminants. It has been reported that carbon nanoparticles had been used as reinforcements showing potential to improve strength, toughness, thermal stability, and electrical/thermal conductivities of the epoxy composites [16,61,63,74].…”
Section: Cfd Analysis Of the Filtration Process Evaluation Of The Dom...mentioning
confidence: 99%